The Potential Role of Aldosterone-Producing Cell Clusters in Adrenal Disease - Lim, Jung Soo; Rainey, William E. (Hormone and Metabolic Research, 2020)
Primary aldosteronism (PA) is the most common cause of secondary hypertension. The hallmark of PA is adrenal production of aldosterone under suppressed renin conditions. PA subtypes include adrenal unilateral and bilateral hyperaldosteronism. Considerable progress has been made in defining the role for somatic gene mutations in aldosterone-producing adenomas (APA) as the primary cause of unilateral PA. This includes the use of next-generation sequencing (NGS) to define recurrent somatic mutations in APA that disrupt calcium signaling, increase aldosterone synthase (CYP11B2) expression, and aldosterone production. The use of CYP11B2 immunohistochemistry on adrenal glands from normal subjects, patients with unilateral and bilateral PA has allowed the identification of CYP11B2-positive cell foci, termed aldosterone-producing cell clusters (APCC). APCC lie beneath the adrenal capsule and like APA, many APCC harbor somatic gene mutations known to increase aldosterone production. These findings suggest that APCC may play a role in pathologic progression of PA. Herein, we provide an update on recent research directed at characterizing APCC and also discuss the unanswered questions related to the role of APCC in PA.
Keywords: primary aldosteronism; aldosterone-producing cell clusters; aldosterone-producing micronodules; cytochrome P-450; CYP11B2